THE ROLE OF INDONESIA NATIONAL MASS MEDIA IN FRAMING THE NEW NUSANTARA CAPITAL CITY - Putra, Anggara Putu Dharma; Kartika, Luh Gede; Agung, I Gusti Ngurah Pertu; Swarthini, Ni Nyoman Ayu; Dananjaya, Cokorda Gede Ari; Chyen, Runita Dewi Chyen; Putri, Made Maheswari Putri (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
The development of the Nusantara Capital City (IKN) is an important milestone in Indonesia's history. The existence of the IKN is expected to encourage inclusive and equitable economic growth throughout Indonesia. The support of the Indonesian people for the IKN is significant. The public obtains information about the IKN through the mass media. The purpose of this study was to examine the way online media presents news regarding Ibu Kota Nusantara (IKN) and to analyze the primary subjects emphasized in the news coverage. The study examines the news subjects related to IKN on the online media platforms Detik.com and Kompas.com utilizing the Latent Dirichlet Allocation (LDA) model and Robert M. Entman's framing technique. The subject analysis yielded 15 primary topics for each media channel. Detik.com mostly covers topics related to politics, investment, IKN construction projects, and accommodation. On the other hand, Kompas.com mainly focuses on investment, the IKN Authority, IKN construction projects, and infrastructure. These themes are the most significant subjects in IKN news coverage across all media platforms, based on their weight and probability. The news framing of Detik.com and Kompas.com is generally characterized by a neutral or favorable tone, to promote public understanding, acceptance, and endorsement of the development of IKN. Favorable media coverage can assist the administration in garnering popular backing and guaranteeing the triumph of the IKN project. Both media outlets present a positive framing on IKN's future and highlight the significance of infrastructure projects in attracting additional investment.